Pemahaman Pelajar Terhadap Bahaya Sampah Plastik Lingkungan Rumah dan Sekolah - Julian Amriwijaya; Sunggoro Trirahardjo; Tutty I. Sodjakusumah (Cakrawala Repositori IMWI, 2023)
The purpose of this study was to determine the understanding of high school students about the dangers of plastic waste in the home and school environment. Some of the indicators used to measure it are students' access to information about the dangers of plastic waste in the home and school environment, adolescent knowledge about the dangers of plastic waste in the home and school environment, attitudes and behavioral control that are internalized. The method used in this study is qualitative with direct interview data collection techniques. The research location is in Bandung with consideration, the number of plastic waste in the city of Bandung is quite high. The results showed that the understanding of high school students about the dangers of plastic waste in the home and school environment. This low understanding is because teenagers do not have a level of concern for waste, especially plastic waste, lack of understanding of students about the harmful effects of plastic waste in the environment and in schools, one of the factors that can be used as suggestions for development is to make efforts to promote the dangers of waste. plastics aimed at high school students in the city of Bandung.